Potato (Solanum tuberosum L.) cultivars physiological, biochemical performance and yield parameters response to acid mine water irrigation and soil physiochemical properties - Rabelani Munyai; David M. Modise (Scientific Reports, 2024)
Abstract This paper aimed to analyse the potato cultivar’s response to physiological, biochemical performance, yield parameters and soil physiochemical properties when subjected to quicklime (un)treated acid mine drainage (AMD) irrigation. A randomized design experiment was conducted with five water treatment levels: TW1; TW2; TW3; TW4 to TW5 replicated four times. The results showed that the quicklime treatment increased the pH of the AMD water, reduced the concentration of EC, NO3 −, SO4 2− and ameliorated heavy metals. However, unsafe levels of heavy metals above the maximum permissible (WHO/FAO) levels were found in Pb, Mg and Mo for water (TW4 and TW5), while As, Cd and Cr for soils (ST4 and ST5) respectively. For potato tubers (TT4 and TT5) concentrations of As, Cd, Cr, and Pb were above the maximum levels. Stomatal conductance, chlorophyll content and yield parameters responded positively by increasing significantly on TW4 and TW5 treatments, but negatively (reduced) towards TW2 and TW3 treatments. A higher bioaccumulation factor was obtained for Zn ˃ Cu ˃ Mg ˃ Pb ˃ Mn, which was an indication of the contamination status of soil, with Zn being more concentrated than other metals. The findings indicate that quicklime-treated AMD is usable for potato irrigation with regular monitoring of heavy metal levels and strict observation of water reuse protocols. The use of this large source of ameliorated (AMD) water will go a long way in improving food security in South Africa and/or in countries where agriculture production is around mining areas.